2012
DOI: 10.1530/erc-11-0354
|View full text |Cite|
|
Sign up to set email alerts
|

The biology and the genetics of Hürthle cell tumors of the thyroid

Abstract: The biology and the genetics of Hü rthle cell tumors are reviewed starting from the characterization and differential diagnosis of the numerous benign and malignant, neoplastic and nonneoplastic lesions of the thyroid in which Hü rthle cell transformation is frequently observed. The clinicopathologic and molecular evidence obtained from the comparative study of the aforementioned conditions indicate that Hü rthle cell appearance represents a phenotype that is superimposed on the genotypic and conventional hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 108 publications
3
68
0
2
Order By: Relevance
“…The WHO defines HCT as a thyroid tumor consisting of at least 75 % of oxyphilic cells within the nodule [1][2][3]. HCT is characterized by the cytoplasmatic accumulation of mitochondria that frequently, on electron microscopy, displays abnormal morphology [1,2,4]. Cytological study subsequent to fine needle biopsy can identify the presence of oncocytic tumor cells, but does not distinguish benign from malignant tumors even though 30 % of HCT are malignant [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The WHO defines HCT as a thyroid tumor consisting of at least 75 % of oxyphilic cells within the nodule [1][2][3]. HCT is characterized by the cytoplasmatic accumulation of mitochondria that frequently, on electron microscopy, displays abnormal morphology [1,2,4]. Cytological study subsequent to fine needle biopsy can identify the presence of oncocytic tumor cells, but does not distinguish benign from malignant tumors even though 30 % of HCT are malignant [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A gene (GRIM-19) locus linked to this familial HCT has been isolated on chromosome 19p13.2 [20]. GRIM-19 gene produces a 16-kDa protein localized within the nucleus and mitochondria [4,12,14,17]. Its function is exerted through two mechanisms: (1) assembly and function of the complex I of mitochondrial respiratory chain and (2) apoptosis induction upon interferon and retinoic acid treatment [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although HCC are believed to be a variant of follicular carcinomas, a more aggressive behavior has been reported (Montone et al 2008, Maximo et al 2012. Considering this and that Hürthle cells show low uptake of iodine and, therefore, do not respond well to conventional treatment (Montone et al 2008), we raised the question as to whether PVALB could be a target for HCC therapy.…”
Section: :9mentioning
confidence: 91%
“…Hürthle cell neoplasms, both benign and malignant, should be composed of at least 75% Hürthle cells (Montone et al 2008), whcih are large cells with abundant cytoplasm containing accumulation of morphologically abnormal mitochondria (Montone et al 2008, Maximo et al 2012, Ferreira-da-Silva et al 2015. Additionally, it has been suggested that Hürthle cell neoplasms may show dystrophic calcifications (Montone et al 2008).…”
Section: :9mentioning
confidence: 99%